The reduced growth due to elevated CO2 concentration hinders the sexual reproduction of mature Northern pipevine (Aristolochia contorta Bunge) - Park, Si-Hyun; Kim, Jae Geun (Frontiers in Plant Science, 2024)
The phenology has gained considerably more attention in recent times of climate change. The transition from vegetative to reproductive phases is a critical process in the life history of plants, closely tied to phenology. In an era of climate change, understanding how environmental factors affect this transition is of paramount importance. This study consisted of field surveys and a greenhouse experiment on the reproductive biology of Northern pipevine (Aristolochia contorta Bunge). During field surveys, we investigated the environmental factors and growth characteristics of mature A. contorta, with a focus on both its vegetative and reproductive phases.In its successful flowering during the reproductive phase, A. contorta grew under the conditions of 40% relative light intensity and 24% soil moisture content, and had a vertical rhizome. In the greenhouse experiments, we examined the impact of increased CO2 concentration on the growth and development of 10-year-old A. contorta, considering the effect of rhizome direction. Planted with a vertical rhizome direction, A. contorta exhibited sufficient growth for flowering under ambient CO2 concentrations. In contrast, when planted with a horizontal rhizome direction, it was noted to significantly impede successful growth and flowering under elevated CO2 concentrations.This hindered the process of flowering, highlighting the pivotal role of substantial vegetative growth in achieving successful flowering. Furthermore, we observed a higher number of underground buds and shoots under the conditions of elevated CO2 concentration and a horizontal rhizome direction instead of flowering. Elevated CO2 concentrations also exhibited diverse effects on mature A. contorta's flower traits, resulting in smaller flower size, shorter longevity, and reduced stigma receptivity, and pollen viability. The study shed light on elevated CO2 concentrations can hinder growth, potentially obstructing sexual reproduction and diminishing genetic diversity.